Dampak Fungsionalitas dan Transparansi pada Optimalisasi Website - Fadila, Ririn Nur; Suryaningrum, Diah Hari (Gorontalo Accounting Journal, 2025)
This study aims to examine and analyze the impact of website functionality on its usability in supporting open government, with transparency as a mediating variable. The research employs a quantitative approach, utilizing primary data collected through questionnaires. The data were processed using the Structural Equation Modeling (SEM) variant-based approach or Partial Least Squares (PLS) with SmartPLS software version 4.0. The findings indicate that website functionality significantly influences both transparency and website usability, and transparency mediates the relationship between functionality and usability. This study highlights the importance of developing responsive website features, supportive technology, and collaboration between governments and communities in digital literacy to achieve transparent and participatory governance.